Characterization of α-Amylase Produced by Different Bacillus spp - A. Alkando, Ahmed; Elamin, Hassan Bashier; Ibrahim, Hanan Moawia (Gezira Journal of Engineering and Applied Sciences; Vol 9 No 2 (2014), 2014)
The production of  the amylase enzyme from different Bacillus spp. was carried out in culture fermentation (SCF). Production of the amylase was carried out for the potential use of the enzyme for industrial purposes. The bacteria used  were isolated and taxonomic characterized from Khartoum state. These bacteria were identified as B megaterium, B. subtilis, B. licheniformis and B. amyloliquefaciens. It was found that Bacillus licheniformis had 6.5 cm zone of clearance, .,B megaterium   cm, B. amyloliquefaciens  cm where as B. subtilis resulted in much lesser  cm. Amylase produced by Bacillus licheniformis B megaterium B. amyloliquefaciens  and   B. subtilis  was 42.64  mg/ml, 38.11 mg/ml, 35.14 mg/ml, and  37.93 mg/ml glucose, respectively.